Peningkatan Kesadaran Hukum Kesehatan melalui Edukasi Partisipatif Pasca UU No. 17 Tahun 2023 di Desa Kadubelang, Pandeglang: Enhancing Health Law Awareness through Participatory Education Following Law No. 17 of 2023 in Kadubelang Village, Pandeglang - Agus Ardinansyah; Mochammad Atmaji Windrianto; Irfan Islami (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Legal awareness regarding patient and healthcare provider rights and obligations remains low, particularly in rural areas of Indonesia. The enactment of Law No. 17 of 2023 on Health has reshaped the legal framework governing patient-healthcare relations, highlighting the need for community education. This community service project aimed to enhance both the public's and healthcare professionals' understanding of their rights and responsibilities under the new law while promoting a participatory health law culture. A participatory approach was employed through interactive lectures, focus group discussions, and the distribution of an educational booklet titled